Advances in chemical constituents and pharmacological effects of Millettia speciosa Champ. - Jingmei CHEN; Xiaofa LYU; Denghui ZHAI; Jinyan CAI (KeAi Communications Co., Ltd., 2021)
Millettia speciosa Champ. is a famous medicinal and edible herb in southeast China. The major constituents of M. speciosa includes flavonoids, alkaloids and so on, which display effects of protecting liver and resisting fatigue. With access to relevant literature, the result shows that the chemical constituents of root and aerial parts in M. speciosa have been studied clearly, while the pharmacological research of M. speciosa is still very preliminary, and there is little application of active constituents for deep pharmacological research and development. Therefore, this paper summarizes the research on the chemical constituents and pharmacological effects of M. speciosa in recent years in order to provide reference for the further development and utilization of M. speciosa active constituents.